Efektivitas Senam Bugar Tehadap Insomnia Pada Lansia di Kelurahan Tambak Sawah Sidoarjo - Riska Rohmawati; Ratna Yunita Sari; Imamatul Faizah; Umdatus Soleha (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2020)
As we get older, the need for sleep in most elderly people tends to decrease. The purpose of the study is to analyze the effect of yoga exercises on insomnia in the elderly in the Sidoarjo Add Sawah Village. This type of research uses a pre-experimental design with one group pretest - posttest design, using a sampling technique that is a total sampling of 30 respondents. 15 groups and 15 intervention groups. Giving fit exercise is done three times a week, in the morning. Data was collected using insomnia rating scale questionnaire before it was done and after the intervention. Then the data were analyzed by Willcoxon and Mann Whitney tests. The results showed that fit exercise was significant in insomnia levels. The results of the test analysis obtained p count of 0.002 in the intervention group and 0.317 in the control group. This means that fit exercise three times a week can reduce insomnia levels in the elderly in the village of Tambak Sawah Sidoarjo. The conclusion of the research shows that fit exercise can reduce insomnia level, for that reason, it should be better in Tambak Sawah village in Sidoarjo to do fitness fit so that the elderly do not experience insomnia.Keywords: Insomnia, Exercise Fitness, Elderly